Safety Culture system elements of Small and Medium-sized Construction Enterprises and its evaluation method - HONGMEI, Jia; JIANWEI, Wang; SUXIA, Liu; LIXIA, Li (PT Keberlanjutan Strategis Indonesia, 2023)
While the construction industry has contributed significantly to the construction of national infrastructure and the enhancement of residents’ living quality, many small and medium-sized construction industries have still been troubled by frequent accidents. Safety accidents have become an essential factor affecting their development of them. The construction of a safety culture is a critical way to solve this kind of problem and enhance the essential safety of these enterprises. Here, adopting the expert survey method, integrating the construction of safety culture with the existing system and work content, an element system of safety culture construction that contains eight primary elements and 32 secondary elements was developed, which could provide a practical and theoretical reference for the construction of safety culture in small and medium-sized construction enterprises. Through the expert survey method and hierarchical analysis method, the weights and sorting of each element were determined, which could guide the construction of enterprise safety culture efficiently. Next, a quantitative evaluation based on a fuzzy comprehensive evaluation of the overall effect of the construction of safety culture was proposed. It could support small and medium-sized construction enterprises to discover the short boards of construction, formulate strategies for continual improvement, and assess the safety culture of construction. Meanwhile, this safety culture system and evaluation method could be a reference for management departments or third-party organizations to manage and evaluate this type of enterprise.